2021
DOI: 10.22219/jk.v12i2.15894
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Covid-19 in the Spiritual, Psychosocial, Physical Aspects and Anxiety Disorders of Health Workers in Hospital

Inna Sholicha,
Aida Ratna Wijayanti

Abstract: Introduction:  The entire world is experiencing the COVID-19  crisis at this time. Hospitals must determine steps to keep treating COVID-19 patients while still provide optimal service by minimizing the risk of COVID-19 transmission. Health workers feel tremendous pressure because of their work. Managing mental and psychosocial health is as essential as maintaining physical care for frontline health workers. Objectives:  The Research aimed to identify the mitigation of COVID-19 from the spiritual, psychosocial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It makes the Madurese people have family relationships and strong emotional ties because they have lived in the same community for a long time. This sense of kinship causes people to ignore health protocols, which makes it challenging to keep their distance and not gather among their families and neighbors (Sholicha, 2021). In the Madura community, sociocultural influences adherence to health protocols.…”
Section: Resultsmentioning
confidence: 99%
“…It makes the Madurese people have family relationships and strong emotional ties because they have lived in the same community for a long time. This sense of kinship causes people to ignore health protocols, which makes it challenging to keep their distance and not gather among their families and neighbors (Sholicha, 2021). In the Madura community, sociocultural influences adherence to health protocols.…”
Section: Resultsmentioning
confidence: 99%
“…While pathologically, one of them is related to pathogenesis, especially during the Covid-19 pandemic, it also supports patient satisfaction. Covid-19 impacts health services and the quality of life for patients and health workers (Sholicha & Ratna, 2021). Several studies have shown that Covid-19 is highly susceptible to respiratory acidosis, especially in pulmonary vascular thrombosis (Diehl et al, 2020;Chen Etchison et al, 2021), cytokine storm, tubular necrosis, and septic shock (Barro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The American Nurses Association 2020 also made a standard operating procedure to provide nurse care plans based on the patient's ethical standard (Association, 2020). Sholicha & Ratna (2021) states that nurses' readiness to mitigate against the COVID-19 pandemic comes from a psychological aspect, as much as 37.5 % (Sholicha & Ratna, 2021). Health workers are at the forefront of health management during the pandemic (Mubarak et al, 2021).…”
Section: Research Themementioning
confidence: 99%